A qualitative study of the reasons for delayed medical treatment in adolescents with depression based on the health ecology model - Yuan Zhao; Yuling Li; Juan Zhao (Frontiers Media S.A., 2023)
BackgroundDepression is a prevalent mental health issue among adolescents, and timely treatment can prevent it from worsening. However, many adolescent depressed patients delay seeking medical treatment. To clarify the reasons for delayed medical treatment in adolescent depressed patients and to provide reference to help adolescent depressed patients to seek medical treatment on time.MethodsFrom July 2022 to March 2023, a semi-structured interview was conducted using a purposive sampling method with adolescent depressed patients attending the Mental Health Center of the First Hospital of Shanxi Medical University. Based on inclusion and exclusion criteria, 22 adolescent depression inpatients with delayed access to medical care were finally included as the study population. This study applied the phenomenological research method in qualitative research and used the Colaizzi seven-step data analysis method to analyze and refine the interview data.ResultsThe study found that 22 adolescents with depression delayed medical care for 1-6 years, with a mean of 2.86 years. Six themes were identified as the reasons for delayed medical treatment: (1) inadequate levels of mental health literacy; (2) lack of disease-related knowledge and information; (3) negative emotional experiences; (4) negative attitudes toward health care; (5) inadequate medical insurance policy for psychotherapy; (6) unequal distribution of resources for mental health medical services.ConclusionThe phenomenon of delayed medical treatment for adolescent depression patients should not be ignored. Efforts should be made to explore the trajectory of delayed illness in adolescents with depression, improve patient symptom assessment, improve poor patient experience, promote positive patient behavior, and improve the current situation of delayed medical treatment for adolescent depression patients through the joint efforts of individuals, families, schools, and society.